Konsep moral dalam Serat Bima Suci karya Yasadipura I - PURWADI, PURWADI (Universitas Gadjah Mada, 2001)
Multidimensional crisis had caused Kraton Mataram to be four small kingdoms. They are Kraton Surakarta, Kraton Yogyakarta, Pura Mangkunegaran and Pura Pakualaman. The kings o f Java did not have significant power. Their position was only as symbol, without authority. Politic and economic suffering had pushed them to shift public attention to literature, art, and culture that fill ethics and mysticism. One o f the literatures that fill ethic and mysticism is Serat Bima Suci. Serat Bima Suci was created by Yasadipura I in the earlier period o f Kraton Surakarta. Historically Serat Bima Suci is still related with kitab Nawaruci that was created by Empu Siwamurti in the end period o f Majapahit Kingdom. Kitab Nawaruci is a literature o f Javanese mysticism that is influenced by Hinduism doctrine. Serat Rima Suci is a literature o f mysticism that has acculturation between Javanism, Hinduism, and Islamism. The harmony o f relation between God, human, and world become focal o f Serat Bima Suci. The relation between human and God theologically has been said as manunggaling kawula gusti a nd curiga manjing warangka. The relation among human and world anthropoecologically has been said as mangasah mingising budi, memasuh mafaning bumi, and memayu hayuning bawana that move to formation o f } alma sulaksana, insan kamil, sarira bathara, a perfect human that has harmonized life between lahir bat in, jiwa-raga, intellectual-spiritual, and head-heart. The expression o f mati sajroning ngaurip in Serat Bima Suci gives persuasive signal to men so that they always eling !an waspada, simple, introspection, to avoid enjoyment o f material, to do lara lapa tapa brata and happy although they are sad. The struggle for life in the world according to Serat Bima Suci connect with the effort to understand sangkan paraning dumadi or from and to where this life, that is khusnul khatimah or the happy ending life. The education o f perfect human character according to Serat Bima Suci is ordered by doing syariat-tarikat-hakikat-makrifat, sembah raga-sembah ciptasbnbah jiwa-sembah rasa. The four o f doctrine are always troubled by human instinct. They are nafsu amarah-lawamah-sufryah, polemos-egocentros-eros. It is only instinct o f mutmainah or religious that support the good conduct, so that men get safety in reaching the purpose o f their life. There are kama-artha-dharma-moksa, enjoyment-prosperity-law-freedom, that all o f them ought to do by examinating the life. There is suffering and difficulty. Some problems o f life according to Serat Bima Suci must be solved wisely, effectively, efficiently, su:fistic professional and religious humanistic as personification o f Bima that reach degree as satria pinandita, that always do tapa ngrame or do social work religiously. The unity between ilmu-amal, cipta-rasa, karsa-karya is the equilibrium to arrange the better future. The reflection o f ethical philosophy existention o f Serat Bima Suci is one o f discourses o f problem solving to some contemporary problems in sociohistorical context.